A percepção da mulher após o exame de papanicolau - Oliviera, Mariana Ferreira (2017)
The objective of this study is to analyze the main causes of non-return of women to receive the results of the Pap smear. An observational, descriptive, cross-sectional and qualitative-quantitative approach was developed through interviews. The study was attended by 19 women users of the Health Unic System (SUS in Brazil) who performed the test and did not return to get the results. The women's speeches were recorded, transcribed and the lexical analysis was performed by the Alceste Software. We classified 154 units of elementary contexts divided into four lexical classes and named according to the meaning they reveal in: motivation to take the exam, cultural influence, conditioning of public policies in order not to get the results and the insertion of women in the public world. The analysis of the perception of women users of the Health Unic System (SUS in Brazil) revealed that, in the current scenario, the insertion in the labor market limits the accomplishment of the examination and the practice of medical treatment, in other words, the examination is performed, but does not instigate them to return to get the results.